2021
DOI: 10.1155/2021/4730936
|View full text |Cite
|
Sign up to set email alerts
|

Research and Analysis on the Influence of Small Clear Distance Drilling and Blasting Method on the Existing Tunnel Structure

Abstract: In order to study the vibration influence of tunnel drilling and blasting method on the built tunnel with small clear distance, taking the intersection of Zhuhai Dahengqinshan No. 1 tunnel and Zhuji urban rail tunnel as the engineering background, we used ABAQUS finite element software to conduct numerical simulation analysis on the influence of different blasting loads on existing tunnels with small clear distance in Zhuji tunnel construction. The following conclusions were drawn: the blasting construction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(1 citation statement)
references
References 18 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Based on the blasting dynamic analysis and weighted double-shear strength criterion, Liu et al [1] studied the impact of ultra-close blasting on existing tunnels, and proposed the nearby blasting safety assessment and blasting scheme preference method. Huang et al [2] used ABAQUS to establish the Zhuji tunnel model, exploring the impact of different blasting loads on the constructed small-clearance tunnels. It concluded that the blasting construction of the under-construction tunnels had the greatest impact on the vaults of existing tunnels.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the blasting dynamic analysis and weighted double-shear strength criterion, Liu et al [1] studied the impact of ultra-close blasting on existing tunnels, and proposed the nearby blasting safety assessment and blasting scheme preference method. Huang et al [2] used ABAQUS to establish the Zhuji tunnel model, exploring the impact of different blasting loads on the constructed small-clearance tunnels. It concluded that the blasting construction of the under-construction tunnels had the greatest impact on the vaults of existing tunnels.…”
Section: Introductionmentioning
confidence: 99%